Inbound and Outbound Open Innovation: Organization and Performances - Michelino,Francesca (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2014)
The aim of the paper is to analyse the relationships between the openness degree of companies and their I) context features, 2) R & D organization and 3) financial performances. The openness degree is defined after a pecuniary approach, involving all the transactions in the innovation market. Hypotheses are formulated and, then, tested on a sample of I26 world top R & D spending bio-pharmaceutical companies for the period 2008-20I2. Open innovation is more pervasive among small and young companies, for most of which it represents the very core business. Inbound and outbound practices have a similar diffusion in terms of number of companies adopting them, but the cumulative values of inbound flows are higher, whereas outbound flows are more relevant when compared to the total business of the firms. Inbound practices are substitutive to internal R & D activities, while outbound ones are complementary to internal development. The performances of companies have an inverted-U shape trend versus inbound practices and a fundamentally decreasing trend versus outbound ones.